The impact of different footwear on running kinematics and jumping stabilization in young healthy athletes - Zech, A.; Argubi-Wollesen, A.; Rahlf, A. L.; Mattes, K.; reer, R. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: Differences between barefoot and footwear situations have been shown for running kinematics or vertical force impact (e.g. Liebermann et al 2010). Based on the hypothesis that barefoot running is more flexible and natural as well as less injurious, the development of minimal (barefoot-like) footwear has recently gained increasing attention. The objective of this study was to compare running kinematics and jumping stabilization time between barefoot and different footwear situations (running socks, Nike free 3.0 and Asics). Methods: The trial was based on a randomized study design. 35 healthy athletes with an experience in long distance running volunteered for participation. The tests were performed under barefoot, running socks (Leguano® barefoot shoes), Nike free 3.0® and Asics GT-2160® conditions in randomized order. The test protocol included two minutes of treadmill running at 8, 10 and 12 km*h-1 in each condition. 3-D kinematic analysis (Vicon Motion Systems) was used to assess ankle and knee joint kinematics as well as cadence and step length during running. Afterwards, the participants performed a unilateral jump-landing task on a force plate in which time to stabilization (TTS) was assessed. Differences between shoe conditions were analyzed by using ANOVA. Results: Significant differences (p<0.001) between all footwear situations were found for ankle and knee kinematics under the three speed conditions. The ankle dorsiflexion at foot strike was highest during barefoot running (e.g. 12 km*h-1: 6.62±5.65°), followed by running socks (8.42±6.01°), Nike free 3.0 (11.00±4.79°) and Asics (12.3±5.1°). Similar results were shown for knee flexion at foot strike as well as cadence and step length during running. No significant differences between all footwear conditions were found for TTS during jump landing. Conclusions: The results showed that with increasing flexibility of footwear there are less differences to barefoot running kinematics. The most barefoot-like condition was shown for the running socks followed by the Nike free 3.0 and Asics. However, the footwear situation seems to have no influence on sensorimotor control during jump landing.